2019
DOI: 10.3389/fpsyt.2019.00837
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Gambling Disorders in Elderly People—A Systematic Review

Abstract: Background: Despite the growth in the number of studies on gambling disorders (GDs) and the potentially severe harm it may cause, problem gambling in older adults is rarely apparent in literature. Driven by the need to overcome this limitation, a broad systematic review is essential to cover the studies that have already assessed the determinants of GD in the elderly.Objectives: The aim of this systematic review is to understand the determinants related to GDs in elderly people.Methods: A total of 51 studies m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 78 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…One of the causes for this descent into poverty had been drinking after retirement. Various surveys have also indicated that drinking and gambling are problems for older men after retirement (Kimura, 2015;Landreat, Cholet, Bronnec, Lalande, & Le Reste, 2019). Midorikawa et al (2019) noted a correlation between a high risk for drinking and poorer help-seeking behavior, suggesting that drinking after retirement inhibits help-seeking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the causes for this descent into poverty had been drinking after retirement. Various surveys have also indicated that drinking and gambling are problems for older men after retirement (Kimura, 2015;Landreat, Cholet, Bronnec, Lalande, & Le Reste, 2019). Midorikawa et al (2019) noted a correlation between a high risk for drinking and poorer help-seeking behavior, suggesting that drinking after retirement inhibits help-seeking.…”
Section: Resultsmentioning
confidence: 99%
“…Midorikawa et al (2019) noted a correlation between a high risk for drinking and poorer help-seeking behavior, suggesting that drinking after retirement inhibits help-seeking. Further, combating boredom and loneliness becomes a factor motivating gambling activities (Landreat et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Given that some participants had not engaged with EGMs the results might have been different if people who more regularly used EGMs were included. Finally, this study did not explore differences according to ethnicity, or socio‐economic status, which will be important for future investigations given the potential links with experiencing gambling‐related harm 44 …”
Section: Discussionmentioning
confidence: 99%
“…The existing studies on older people suggest that problems related to gambling are more likely to develop among women (Guillou-Landréat et al, 2019;Moccia et al, 2017), to decline with age (Guillou-Landréat et al, 2019) and to be related to issues such as poor mental and physical health (Desai et al, 2004;Vander Bilt et al, 2004), the decline of executive functioning and the impairment of favourable decisionmaking (Ariyabuddhiphongs, 2012). However, a considerable body of research demonstrates that the well-being of the elderly is significantly influenced not only by their physical health but also by the quality of their relationship with family members and community.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, most of the studies were conducted in North America: the United States or Canada. Few have been conducted in Europe (Guillou-Landréat et al, 2019), and a concomitant lack of attention has been paid to non-Anglo-Saxon groups.…”
Section: Introductionmentioning
confidence: 99%